KANDUNGAN TOTAL ZAT PADAT TERSUSPENSI (TOTAL SUSPENDED SOLID) DI PERAIRAN RAHA, SULAWESI TENGGARA - Tarigan, M S; Edward, Edward (UI Scholars Hub, 2003)
Total Suspended Solid Content in Raha Waters, Northeast of Celebes. Measurement on Total Suspended Solid (TSS) in Raha waters were carried out in May 2001. The results showed that the content of total suspended solid varied between 74,8 – 78,9 ppm with averages content is 76,5 ppm. This content is still suited to the threshold value stated by government decree in 1988 for fishery and sea conservation park, but not suitable for recreation (swimming, diving activity).